Boundary value problem for the fractional-loaded Lavrent’ev-Bitsadze equation - Attaev, A.Kh.; Iskakov, S.A.; Ramazanov, M.I. (Bulletin of the Karaganda University. Mathematics Series, 2017)
In this paper we study the boundary value problem for a fractional - loaded Lavrent’ev-Bitsadze equation in a rectangular domain with nonlocal boundary conditions. Similar boundary value problems were studied in papers [1-3]. The problem studied in this paper differs from the problems considered earlier in that, firstly, the domain in the hyperbolic part is not characteristic, and secondly, there are fractional - loaded terms in the equation, which makes it possible to reveal certain features of the problem under consideration.